Analisis Hambatan Guru dalam Penerapan Model PBL pada Pembelajaran PAI di SMP Darul Hikmah Pagutan Mataram - Rahman, Zidan Fitrayadi; Arifin, Syamsul (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2024)
The problem based learning (PBL) model is very suitable for use in Islamic religious education (PAI) learning in schools. This PBL model links subject matter to students' daily life situations, however in its application this PBL model does not always work effectively but there are several obstacles experienced by teachers. This article aims to analyze teachers' obstacles in implementing the problem based learning (PBL) learning model in PAI learning at Darul Hikmah Pagutan Mataram Middle School. This research uses qualitative research methods with a descriptive approach. Data collection uses the Miles and Huberman framework by means of data condensation, data presentation, and data verification. The results of this research show that the obstacles for teachers in implementing the PBL model in PAI learning at Darul Hikmah Pagutan Mataram Middle School are hampered by the lack of facilities and infrastructure that support PBL model learning, lack of teacher readiness because they have additional duties as school administrators, limited study time, and Students' thinking abilities are not the same because each student has a different background.